STEM Education-Based Learning Management for Creative Thinking Development: Length Measurement Lessons of Grade 3 Students - Parichart Prasertsang; Autchareya Komal; Sayfon Nilvon; Wittaya Worapun; Yuttachak Lamjuanjit (Journal of Educational Issues, 2024)
The main purpose of this research was to develop 3rd grade students’ creativity to meet a criterion of 70% by using the STEM Education-based learning management. The target sample included six 3rd grade students of Dongsankaewdongsamran School, Chanuman District, Amnat Charoen Province, Thailand. This research took place in the second semester in the academic year 2020. The design of this research was action research conducted in two cycles. The research instruments were 1) two lesson plans based on the STEM Education-based learning management, 2) the Torrance Test of Creative Thinking (TTCT), 3) a student behavior observation form, and 4) an interview form. Statistics for data collection were mean and percentages. The results showed that in cycle 1 the STEM Education-based learning management improved four students (66.67%) to pass the criterion of 70%. In cycle 2, two students passed the criterion of 70%. All of them finally passed the criterion (100.00%). In conclusion, the STEM Education-based learning management can promote and develop students’ creativity in each cycle.